ANALISIS POTENSI PENGEMBANGAN OBJEK WISATA SUNGAI BATANGHARI DI KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Yusmiono, Boby Agus; Januardi, Januardi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The Batanghari River is a flow of the Musi River which is located in the Banyuasin district, one of the areas in the South Suamtera Province. The potential of river tourism that is owned by the area is very large, with natural charm that is still beautiful river boundary covered with aquatic plants such as scattering tapestries, adding to the uniqueness and diversity that is fascinating and rarely found elsewhere. During this time the development of tourism objects in the area has not been managed optimally because of several obstacles that hinder the development of each river tourism object. The method in this study is descriptive qualitative. Descriptive because this study aims to describe the phenomenon of attractions in a systematic, factual, and accurate manner regarding the facts and the relationship between phenomena. Based on the results of the analysis of each tourist attraction, the Batanghari River has a high level of potential category with most of the river attractions that can be optimized are swamp buffalo attractions, and the beauty of river trunks that have the highest value. The results show that the supporting factors of the Batanghari river tourism object have not been well promoted, in the case that the area is not far from the city center, can be reached within 90 minutes from the city of Palembang. Other supporting factors are beautiful and pristine natural panorama, openness of society towards tourists, good security conditions, and a variety of uniqueness, as well as riverbanks that can reconcile the heart. The inhibiting factors that lead to river tourism are the limited facilities and infrastructure of tourist objects, the lack of public transportation to reach these attractions, the lack of public awareness to make the area a tourist attraction (professional HR to manage tourism objects), the absence of tourism promotion or less take advantage of technological advancements.